2000
DOI: 10.1016/s0006-3495(00)76650-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Polyethylene Glycol on the Mechanics and ATPase Activity of Active Muscle Fibers

Abstract: We have used polyethylene glycol (PEG) to perturb the actomyosin interaction in active skinned muscle fibers. PEG is known to potentiate protein-protein interactions, including the binding of myosin to actin. The addition of 5% w/v PEG (MW 300 or 4000) to active fibers increased fiber tension and decreased shortening velocity and ATPase activity, all by 25-40%. Variation in [ADP] or [ATP] showed that the addition of PEG had little effect on the dissociation of the cross-bridge at the end of the power stroke. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 61 publications
4
25
2
Order By: Relevance
“…No significant difference in activity has been observed for lysozyme attached via a spacer compared to lysozyme directly attached to nanoparticle surface. This result was somewhat contradictory to our expectations because previous research (Chinn et al, 2000;Lee and Kim, 2002) demonstrated a beneficial effect of attachment via spacer on activity of immobilized enzymes. This effect was attributed to reduced interaction of the enzyme with the surface of its support due to the presence of the spacer.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…No significant difference in activity has been observed for lysozyme attached via a spacer compared to lysozyme directly attached to nanoparticle surface. This result was somewhat contradictory to our expectations because previous research (Chinn et al, 2000;Lee and Kim, 2002) demonstrated a beneficial effect of attachment via spacer on activity of immobilized enzymes. This effect was attributed to reduced interaction of the enzyme with the surface of its support due to the presence of the spacer.…”
Section: Discussioncontrasting
confidence: 99%
“…1B). Since attachment via PEG spacers minimizes interactions of immobilized protein with the support (Chinn et al, 2000;Lee and Kim, 2002), lysozyme conjugated to nanoparticles via PEG spacers was expected to show higher enzymatic activity. The conjugation protocol, enzyme and nanoparticle concentrations, and purification methods were similar to those described above for the glutaraldehyde-based attachment.…”
Section: Protein Conjugation To Aminated Nanoparticlesmentioning
confidence: 99%
“…We note that the increase in P i dependence shown for DMSO and ethylene glycol contrasts markedly with data obtained recently using poly(ethylene glycol) 4000. This polymer of ethylene glycol increased isometric tension in skinned fibres in the presence of different concentrations of P i , without affecting P i affinity [68].…”
Section: Discussionmentioning
confidence: 86%
“…The pre-power stroke cross bridges would not produce substantial isometric force, but large forces when stretched, and could be responsible for low ATP hydrolysis commonly observed in experiments (Abbott et al 1951;Linari et al 2003). Studies using permeabilized fibres from mammalian muscles treated with phosphate analogues suggest that this may be the case, as the stretch-isometric force ratio obtained at the transition point increases when cross bridges are biased into pre-power stroke states (Getz et al 1998;Chinn et al 2000Chinn et al , 2003. However, in a more recent study, these results were not confirmed by Bagni et al (2005), who treated intact fibres from frog muscles with the phosphate analogue 2,3-butanedione monoxime (BDM) and observed that the stretch-isometric force ratio was not changed.…”
Section: K1mentioning
confidence: 99%